Using IBM SPSS Statistics for research methods and social science statistics - Wagner, William E (London, 2013)
Ideal either as a companion to a traditional statistics or research methods text or as a stand-alone guide, Using SPSS for Research Methods and Social Statistics is a useful reference for those learning to use the SPSS software for the first time or those with only basic knowledge about SPSS. This student-friendly resource shows readers how to use images and directions drawn from SPSS Version 20 and now uses the latest version of the General Social Survey (GSS, 2010) as a secondary data set.
Keywords: Social sciences-Statistical methods